The Adaptation of Ivana Šojat’s Modernist Novel Unterstadt - Koprolčec, Dina; Živić, Tihomir (Anafora, 2023)
Written in 2009, Unterstadt is a modernist novel by Ivana Šojat, an Osijek-based author, prone to writing about topics she discovers in the archives. The novel is a familial saga portraying four main female characters throughout different generations; it is a narrative of dreams, hopes, philosophies, and tragedies related to the lifetime of each respective generation. Likewise, it is a story of faith and free will of the protagonists who have testified to a change in politics on the territory of ex-Yugoslavia, from World War I up to the initial decades of the twenty-first century. Thus, the novel is intertwined with the intermezzi of silence and tales untold because of the fear that affected each generation of the family. Very well-received and acclaimed by the critics and readership alike, Unterstadt was also adapted into a theatrical play, dramatized by Nives Madunić Barišić and Zlatko Sviben, in the production of the Croatian National Theater in Osijek. It premièred on July 29, 2012, the first day of the annual Osijek Summer of Culture manifestation. As the production was extremely demanding, the paper will examine the novel’s adaptation into an awarded masterpiece of the Croatian theater in view of the contemporary theory and practice of dramatization and theatrical adaptation, complemented by the elements of New Historicism, fragments of Miroslav Krleža’s play In the Camp (U logoru), and authentic historical documents dating from World War I up to the present day.